(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Topicality of the project consists in the requirement of search and use of effective pedagogical technologies for successful training in skills of students with the help of games. In qualification, the project offered the final, which is applied attempt as by effective methods of communicative competence. The purpose and objectives of the project consists in the reasons and approval of communicative actions as one of effective methods